(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: The potential to predict metaphase II (MII) oocyte yield in controlled ovarian stimulation (COS) has not been elucidated, despite being a mandatory predictor of fertilization potential. Hence this area is marred by the diversity of approaches to ovarian stimulation and the deficiency of standards. Objective: To determine the role of serum anti-Müllerian hormone (AMH) as a predictor of MII oocyte yield during controlled ovarian stimulation at a private fertility clinic in Nairobi. Methods: A retrospective descriptive cohort study design was employed in which MII outcomes during COS were compared among women aged 18-45 years with normal or low serum AMH levels. Data were collected sequentially until the desired sample size was achieved. Data were analyzed using the IBM statistical package for social sciences (SPSS) version 24.0 and STATA version 15. The level of significance was set at p<0.05. Results: Approximately one-third of women above 35 years of age had normal serum AMH levels, while nearly three-quarters had low serum AMH levels (OR=0.1; 95 CI (0.1–0.4); p-value<0.001). By day % five, hyperresponse was more preponderant among those with normal AMH levels (39.0 vs. 3.8 ; % % OR=15.9; CI (2.0-126.0); p-value<0.001) and remained consistent. Almost three quarters of women with low AMH levels had a low MII yield compared to nearly one-quarter of those with normal AMH levels (OR=0.3; 95 CI (0.1-0.8); p- % value=0.014), even after controlling for age. This trend was consistent with that of the total oocyte count. The sensitivity, specificity, and positive and negative predictive values of serum AMH level as a predictor of MII oocyte yield were 86.0 , 54.3 , % % 72.96 , and 73.1 , respectively. % % Conclusion: Normal serum anti-Müllerian hormone levels is associated with increased follicular count and total oocyte harvest during controlled ovarian stimulation and is a good predictor of MII oocyte yield.